Pengaruh Transformasi Digital Terhadap Kinerja Keuangan Yang di Mediasi oleh Pengalaman Pelanggan, Big Data Analytics, Penganggaran dan Pengendalian Anggaran serta Moderator Efisiensi Keuangan pada UMKM di Kota Semarang - Nor Dafa Farida; Suci Khoirio Atiningsih (Universitas Katolik Soegijapranata, Semarang, 2026)
This study aims to examine the effect of digital transformation on MSMEs’ financial performance by incorporating customer experience, big data analytics, and budgeting and budgetary control as mediating variables, as well as financial efficiency as a moderating variable. This study employs a quantitative approach using a survey of 93 MSMEs in Semarang City. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software, grounded in Socio-Technical Systems Theory and Dynamic Capability Theory. The results indicate that digital transformation has a significant effect on big data analytics but does not directly affect customer experience or budgeting and budgetary control. Big data analytics and customer experience positively influence budgeting and budgetary control, which subsequently improves MSMEs’ financial performance. In addition, financial efficiency is found to strengthen the relationship between budgeting and budgetary control and financial performance.